Use of Interactive Digital Posters as an Innovative Learning Technology in Ukrainian Higher Education (on the example of the course "Children's Literature and Methods of Teaching Literary Reading" ) - Olga Derkachova; Solomia Ushnevych (Vasyl Stefanyk Precarpathian National University, 2022)
The article analyses the ways of making a successful graduate - a future New Ukrainian School teacher. One of the key competencies, interrelated with values, linguistic and literary, is outlined. It is emphasized that at the present stage of development of language education a significant role is given to the technological approach to the organization of the educational process. Effective modern teaching aids that help present educational material in a different way are analyzed; arouse students' interest; contribute to the development of a future teacher's creative potential. They are convenient and effective to use, facilitating the work of both teachers and students. This is an innovative form in the lecture structures, practical classes, as well as independent work, school teaching practice. The study focuses on the peculiarities of creating interactive posters and their importance in the reception of fiction texts. The text of the article contains interactive digital posters created by students of speciality "Primary education" of Vasyl Stefanyk Precarpathion University with some illistrations that are free available on the Internet.